Biosimilar insulins are coming: what they are, what you need to know. (November 2014) - Edelman, Steven; Polonsky, William H.; Parkin, Christopher G.
Abstract Background: Many branded analog insulins will lose patent protection during the next few years. In response, a number of companies are developing biosimilar insulins, which have the potential to lower healthcare costs and increase patient access. Although these products are not yet available in the US, it is important that patients, payers and clinicians be aware of the potential benefits as well as concerns associated with biosimilar insulins. Scope: This report provides information about these new products and discusses key questions clinicians should consider regarding biosimilar insulin. Conclusion: The biosimilar insulins being developed have the potential to provide clinical benefits that are similar to current insulin analogs at a more affordable price, thereby allowing more patients greater access to these effective therapies. However, industry and regulatory agencies must proceed with caution in bringing these new insulins to market. Clinicians must be aware of how availability of these new medications may impact patients' adherence to their treatment regimens and begin taking steps now to address these potential issues.